2018
DOI: 10.4155/fmc-2017-0217
|View full text |Cite
|
Sign up to set email alerts
|

Second-Generation Nitazoxanide Derivatives: Thiazolides are Effective Inhibitors of the Influenza a Virus

Abstract: Aim:The only small molecule drugs currently available for treatment of influenza A virus (IAV) are M2 ion channel blockers and sialidase inhibitors. The prototype thiazolide, nitazoxanide, has successfully completed Phase III clinical trials against acute uncomplicated influenza.Results: We report the activity of seventeen thiazolide analogs against A/PuertoRico/8/1934(H1N1), a laboratory-adapted strain of the H1N1 subtype of IAV, in a cell culture-based assay. A total of eight analogs showed IC 50 s in the ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 31 publications
0
40
0
Order By: Relevance
“…Yellow fever virus IC 50 , 0.06 μg/ml TIZ [24] Japanese encephalitis IC 50 , 0.12 μg/ml NTZ [25] Several in vitro studies revealed that TIZ caused inhib- The half maximal inhibitory concentration of TIZ against influenza viruses ranged from 0.2 to 1.5 μg/ml [9]. It was also reported that IAV is not likely to develop resistance to TIZ since thiazolides do not have a direct action against viral RNA or protein [30], and it is reported that the development of viral resistance to the antiviral drugs that target host cell is less expected when compared to virus-specific inhibitors [31]. Moreover, a synergistic antiviral effect was observed upon combining NTZ with oseltamivir or zanamivir against influenza A/H1N1-PR8 and the avian A/H5N9 [32].…”
Section: Nitazoxanide and Coronavirusesmentioning
confidence: 99%
“…Yellow fever virus IC 50 , 0.06 μg/ml TIZ [24] Japanese encephalitis IC 50 , 0.12 μg/ml NTZ [25] Several in vitro studies revealed that TIZ caused inhib- The half maximal inhibitory concentration of TIZ against influenza viruses ranged from 0.2 to 1.5 μg/ml [9]. It was also reported that IAV is not likely to develop resistance to TIZ since thiazolides do not have a direct action against viral RNA or protein [30], and it is reported that the development of viral resistance to the antiviral drugs that target host cell is less expected when compared to virus-specific inhibitors [31]. Moreover, a synergistic antiviral effect was observed upon combining NTZ with oseltamivir or zanamivir against influenza A/H1N1-PR8 and the avian A/H5N9 [32].…”
Section: Nitazoxanide and Coronavirusesmentioning
confidence: 99%
“…Nitazoxanide is an antiprotozoal drug used to treat Cryptosporidium and Giardia infections. In vitro data demonstrate antiviral activity against influenza A and B strains (195,196). It acts by inhibiting influenza HA trafficking through the epithelial endoplasmic reticulum and Golgi apparatus and preventing maturation by blocking HA terminal glycosylation (197).…”
Section: Targeting Iav and S Pneumoniae At The Mucosal Barriermentioning
confidence: 99%
“…A phase 2b/3 trial of nitazoxanide in uncomplicated influenza was well-tolerated and showed reduced symptoms and viral loads (198). A randomized placebo-controlled phase III trial was completed in March 2019 and remains currently unpublished (196). If approved, this drug, through its primary targeting of the virus, will also affect the local immune responses to the virus initiated by the respiratory epithelial cells as detailed above.…”
Section: Targeting Iav and S Pneumoniae At The Mucosal Barriermentioning
confidence: 99%
“…Several modiଏcations aimed to replace the reactive nitro group of NTZ with halides. Thus, bromo-and chloro-thiazolides are currently investigated for their antiviral and anticancer activity [27,[32][33][34][35][36]. On the background of increasing antibiotic resistance [37,38] and cumulating knowledge about the relevance of a healthy microbiome in the regulation of intestinal homeostasis [39,40], thiazolides lacking antibiotic effects appear to be the preferred lead compounds for anticancer treatment.…”
Section: Introductionmentioning
confidence: 99%